The Influence of Work Motivation and Work Discipline on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Prima Mas Lestari (PML) in Bungo Regency, Jambi - Apriani, Mita; Jhon Veri; Ramdani Bayu Putra; Hasmaynelis Fitri (Indonesian Journal of Economic & Management Sciences, 2024)
This research aims to find out how much influence work motivation and work discipline have. The research variables are Work Motivation (X1), Work Discipline (X2), Employee Performance (Y) and Job Satisfaction (Z). The data collection method is through surveys and distributing questionnaires to employees as respondents. The analysis method used is the outer model and inner model test using the smart PLS 3.0 data processing tool. The research results show (a) Work Motivation has a significant positive effect on Job Satisfaction of 8,152 with a significant level (0.000 < 0.05) (b) Work Discipline has a significant positive effect on Job Satisfaction of 2,918 with a significant level (0.069 < 0.05) (c) Work Motivation has a positive and insignificant effect on Employee Performance of 1,460 with a significant level (0.002< 0.05) (d) Work Discipline has a positive and significant effect on Employee Performance of 3,111 with a significant level (0.000< 0.05) (e) Job Satisfaction has a positive and significant effect significant effect on Employee Performance of 8,152 with a significant level of (0.047< 0.05) (f) Work Motivation has a positive and significant effect on Job Satisfaction through Employee Performance of 2,600 with a significant level of (0.078> 0.05) (g)